2021
DOI: 10.14569/ijacsa.2021.0120839
|View full text |Cite
|
Sign up to set email alerts
|

Usability Perceptions of the Madrasati Platform by Teachers in Saudi Arabian Schools

Abstract: As a result of the COVID-19 pandemic, the Saudi Ministry of Education launched the Madrasati Platform for distant teaching and learning for schools. Therefore, recognizing the design and the usability challenges that are linked to this new platform is significant. This paper reports the results of a study that examines the usability level of the Madrasati Platform from the perspectives of the schoolteachers in Saudi Arabia. It also investigates the usability issues that teachers faced when using the platform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, other obstacles to using Madrasati were teachers' lack of digital skills and skills in teaching with technology, particularly e-assessment and student e-learning activities (Alessa, 2022). Shishah (2021) found that Madrasati needs improvements from the teachers' point of view, particularly its navigation. Furthermore, Ospina et al (2021) suggested that it would be great if Madrasati had features that allowed teachers to communicate with each other.…”
Section: Context Of the Studymentioning
confidence: 99%
“…In addition, other obstacles to using Madrasati were teachers' lack of digital skills and skills in teaching with technology, particularly e-assessment and student e-learning activities (Alessa, 2022). Shishah (2021) found that Madrasati needs improvements from the teachers' point of view, particularly its navigation. Furthermore, Ospina et al (2021) suggested that it would be great if Madrasati had features that allowed teachers to communicate with each other.…”
Section: Context Of the Studymentioning
confidence: 99%
“…Managing these schools necessitates qualified teachers and a modern learning management system (LMS), such as Madrasati (M). The M LMS is an e-learning system with several tools that reinforce all educational levels' teaching and learning processes (Shishah, 2021). Following COVID-19, M LMS technology was introduced in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Madrasati Learning Management System is among the latest in a series of global Learning Management Systems. It is defined as a web-based electronic learning environment comprising various tools that support the teaching and learning process across all education levels, from first grade to grade 12 (Shishah, 2021). Therefore, Madrasati Learning Management System shares similarities with many international Learning Management Systems in terms of its concept.…”
Section: Introductionmentioning
confidence: 99%